2021
DOI: 10.1177/1096348020987273
|View full text |Cite
|
Sign up to set email alerts
|

The Factor Structure of Medical Tourist Satisfaction: Exploring Key Drivers of Choice, Delight, and Frustration

Abstract: The current study intends to contribute to a better understanding of the medical tourism experience. In particular, this study uses data from a survey-based study conducted on a sample of 1,209 medical tourists in Croatia. On the one hand, this study aims to explore and shed light on the decision-making process of medical tourists, and, on the other hand, to reveal which elements of both the medical institution and the destination where it is located, have largest potentials to drive medical tourist delight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Studies by [53] established that tourist satisfaction forms a greater decision in embarking on tourism. The results of the current tourist's satisfaction and tourism destination decision-making are also affirmed by [46] [55] [56]. This means that there is a significant relationship between social media, tourist satisfaction, and tourism destination decision-making.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies by [53] established that tourist satisfaction forms a greater decision in embarking on tourism. The results of the current tourist's satisfaction and tourism destination decision-making are also affirmed by [46] [55] [56]. This means that there is a significant relationship between social media, tourist satisfaction, and tourism destination decision-making.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 93%
“…A recent study was conducted by [55] on tourists' destination choice and satisfaction through emotional involvement; the study collected data from 382 domestic tourists and concluded that destination attributes such as site attraction, accommodation, and transportation have a significant influence on tourist satisfaction. The studies by [56] argued that tourist satisfaction and tourist delight lead to sustainable performance. The study added that food and beverages have a positive effect on tourist satisfaction.…”
Section: Tourist Satisfactionmentioning
confidence: 99%
“…Ban & Kim (2020) menemukan enam dimensi yang memengaruhi niat berkunjung ke Korea untuk medical tourism, termasuk kerentanan, keparahan, hambatan, dan manfaat. Mikulić et al (2021) mengidentifikasi faktor pendorong kepuasan pasien dalam medical tourism, seperti kualitas perawatan dan rasio harga. Damayanti et al (2021) menyoroti atribut kredibilitas rumah sakit dan kemampuan menyediakan pelayanan kesehatan yang professional dalam medical tourism Malaysia.…”
Section: Tabel 2 Strategi Dan Hasil Pencarian Artikel Jurnal Database...unclassified
“…Tandon (2021) stated that a consumer satisfied with the product/service would get delighted. Consumer satisfaction, when exceeding the expectations, leads to consumer delight (Mikulić et al, 2021). Mattila and Ro (2008) recommended that the buyer gets disappointed by anger, regret, and outrage.…”
Section: Consumer Satisfaction With Consumer Delight Consumer Regret and Outragementioning
confidence: 99%